Arctiin alleviates the progression of osteoarthritis by regulating the cholesterol metabolic pathway - Jiale Mai; Jiacong Xiao; Yanhuai Ma; Dawei Gong; Jianliang Li (Scientific Reports)
Abstract Osteoarthritis (OA) is a multi-factorial degenerative joint disease with unclear pathogenesis. Conservative treatments, primarily aimed at pain relief, fail to halt disease progression. Metabolic syndrome has recently been implicated in OA pathogenesis, underscoring the need for novel therapeutic strategies. Arctiin (ARC), a lignan known for its anti-inflammatory and anti-osteoporotic properties, has potential effects on OA that merit exploration. We assessed ARC’s impact on chondrocyte viability using the Cell Counting Kit-8 and toluidine blue staining for glycosaminoglycan presence. Gene and protein expression were analyzed via RT-PCR, Western blotting, and immunofluorescence. An OA rat model was employed for in vivo evaluations through histological assessments and micro-CT scanning. ARC reversed IL-1β-induced upregulation of MMP3, MMP13, and COX-2 and the downregulation of collagen II and SOX9. It modulated cholesterol metabolism in IL-1β-stimulated chondrocytes by inhibiting the CH25H-CYP7B1-RORα axis, reducing cartilage damage and proteoglycan loss in OA rats, and effectively inhibiting subchondral bone osteolysis. ARC inhibits IL-1β-induced inflammatory responses and ECM degradation, suggesting its potential as a therapeutic agent for OA. It acts partly by modulating cholesterol metabolism and suppressing the CH25H/CYP7B1/RORα axis in chondrocytes.